Concrete anti-cracking agent suitable for high-temperature environment as well as preparation method and application of concrete anti-cracking agent
By using composite expansion agents of calcium oxide, magnesium oxide and hydration heat-regulating materials in high-temperature environments, cracking problems caused by hydration exothermic and shrinkage in high-temperature and large-volume concrete structures are solved, and effective temperature shrinkage and crack risk control is achieved.
Patent Information
- Application Number
- CN202311371101.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to effectively solve the cracking problems caused by hydration and exothermic and shrinkage in high-temperature and large-volume concrete structures. Especially in high-temperature environments, the commonly used cracking measures have limited effects or are difficult to promote.
Concrete anti-cracking agents including calcium oxide expansion materials, magnesium oxide expansion materials and hydration heat regulation materials are used to form composite expansion agents suitable for high-temperature environments by limiting the particle size and component ratio, thereby achieving compensation for shrinkage throughout the process and reducing the risk of cracking.
It effectively inhibits the hydration and heat release rate of cement concrete, reduces the risk of temperature shrinkage and cracking, and is suitable for cement hydration in high temperature environments, avoiding the long and slow-setting phenomenon caused by the hydration heat-regulating materials at high temperatures.
Smart Images

Figure CN119898985A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical building material admixtures, and in particular relates to a concrete anti-cracking agent suitable for high-temperature environments, a preparation method and an application thereof. Background Art
[0002] Concrete is the most widely used building material in the world today, and is widely used in engineering fields such as municipal engineering, bridges, roads, railways, urban rail transit, tunnels, dams, etc. Cement, as the most widely used cementitious material in concrete, firmly binds aggregates such as sand and stone together by reacting with water, thereby generating strength. Strength is the most important and basic indicator of concrete. Generally speaking, after pouring concrete, it is hoped that the strength will increase as quickly as possible, which has the advantages of accelerating the turnover efficiency of the formwork, shortening the construction period, and reducing costs. As concrete structures develop towards super-high and large volumes, and the service environment becomes increasingly harsh, the strength grade of concrete is getting higher and higher, which requires more cement and other cementitious materials. As the amount of cement increases, the strength increases, resulting in an increase in hydration heat release and shrinkage; this causes the concrete to exhibit the characteristics of high temperature rise and large shrinkage, thereby increasing the risk of cracking due to temperature shrinkage and chemical shrinkage.
[0003] In actual construction, in order to balance the contradiction between concrete strength grade and cracking risk, measures are generally taken from the aspects of materials, mix ratio and construction. In terms of materials, medium and low heat cement can be used to reduce the heat of cement hydration, and anti-cracking functional materials can be used. In terms of mix ratio, fly ash, slag, silica fume and other admixtures can be used to replace part of the cement to reduce the hydration heat. In terms of construction, the temperature of raw materials can be lowered, ice can be added to reduce the temperature of concrete mixing, or cooling water pipes can be added to take away the hydration heat in time.
[0004] Among the above measures, medium and low heat cement is difficult to produce and expensive, and it is difficult to promote it in ordinary projects. Too high a proportion of fly ash replacing cement will reduce the early strength. More importantly, good quality fly ash is becoming less and less. Slag and silica fume have little effect on strength, but they will increase shrinkage, which is not conducive to crack resistance. Adding ice to lower the temperature of raw materials and concrete requires additional ice-making equipment or additional cooling equipment, which consumes a lot of energy and has limited effect. The process of adding cooling water pipes increases the construction process on the one hand, and on the other hand, the joints of the cooling water pipes are easily damaged by the concrete falling during pouring or damaged by the vibrator, resulting in water leakage and other problems. In addition, the cracking may be aggravated due to improper control of water temperature and water flow.
[0005] In summary, combined with the actual engineering situation, the use of anti-cracking functional materials is the most convenient and economical anti-cracking measure. Different anti-cracking functional materials can be used for different cracking causes. Due to plastic cracking or drying shrinkage caused by water evaporation, there are functional materials that reduce water evaporation, or functional materials with shrinkage reduction are used. For example, CN105503019B and CN101805145B disclose water evaporation inhibitors with reduced plastic shrinkage cracking and their preparation methods. CN103450415B and CN102030872A disclose functional materials with shrinkage reduction and their preparation methods. For self-shrinkage, expansion materials with compensating shrinkage can be used, such as calcium oxide, calcium sulfonate or composite expansion source expansion agents. CN101774777B, CN104692690A, CN104671688B, CN104671694B and CN104692691B and other patents disclose expansion agents with calcium oxide as expansion source and their preparation methods. For the shrinkage in the later stage of temperature drop, a light-burned magnesium oxide expansion agent with delayed expansion can be used. CN101786819A, CN101643333B, CN108314335A, CN108455883A and CN108483950A disclose the preparation, use and preparation device of different active magnesium oxides. For the temperature shrinkage caused by the fast heat release rate of cement hydration, a hydration heat inhibition material can be used. CN104609766A, CN104710132A, CN103833259B, CN104098288B, CN103739722B and CN105712647A disclose technical solutions that polysaccharide structured dextrin has the function of regulating the heat of cement hydration. The preparation methods disclosed in these patents mostly use chemical reagents to react chemically with dextrin, monosaccharide or sugar alcohol compounds with known large molecular weight to achieve the effect of weakening the slow setting of dextrin.
[0006] The cracking of concrete in actual engineering structures is affected by the combined effects of multiple factors, and composite expansive agents with multiple functions are generally used. Engineering experience shows that the combined use of hydration heat regulating materials with the function of inhibiting cement hydration regulation, calcium oxide and magnesium oxide expansive agent materials with full-process compensation can effectively solve various concrete cracking problems. However, different hydration heat regulating materials, calcium oxide and magnesium oxide expansive materials have different performances, and only product combinations with excellent performance can be effective. The particle size of calcium oxide materials has a significant effect on the expansion performance, and the particle size and activity value of light-burned magnesium oxide correspond to different expansion stages. Hydration heat regulating materials are generally starch dextrin products. In addition to the basic parameter of molecular weight, the performance of products prepared by different methods varies greatly. The natural three-dimensional structure of starch is destroyed at high temperature, resulting in poor hydration heat regulation performance and more serious slow setting.
[0007] CN107313463B discloses a technical solution for using a calcium-magnesium composite concrete anti-cracking agent; CN102674738B discloses a multifunctional anti-cracking admixture comprising calcium oxide expansion clinker, dextrin and fly ash and a preparation method thereof; CN111377653B discloses an anti-cracking agent comprising a calcium expansion component and a zeolite component with a surface film and a cement hydration heat regulating material liquid in the pores; CN108147705B discloses an anti-cracking agent formed by a cement hydration heat regulating component and a magnesium expansion component; CN111377648B discloses a magnesium-based, temperature- and humidity-controlling high-efficiency anti-cracking agent for cement concrete with a temperature-sensitive material coated on the surface and a preparation method and application thereof; The concrete anti-cracking control method disclosed in CN116674052A not only uses an anti-cracking agent, but also sprays a moisture evaporation inhibitor with the function of inhibiting plastic cracking after construction. These patented technologies only provide two of the three key components, hydration heat regulation materials, calcium oxide and magnesium oxide. They are suitable for structural concrete with a lower risk of cracking, but cannot solve the cracking problem of complex structural concrete with high temperature, large volume, etc. with a higher risk of cracking.
[0008] CN110655344B discloses an anti-cracking admixture including a hydration heat regulating material, a shrinkage-reducing high-performance polycarboxylic acid powder; a water-absorbing resin, a water evaporation inhibitor, and a full-process compensating expansion component. The anti-cracking agent disclosed in CN111441246A, CN111848019A, and CN113929346A includes an expansion material and a hydration heat temperature rise regulating material, wherein the expansion material is a composite of calcium oxide and magnesium oxide. The above patents generally only limit the molecular weight or performance index of the corn starch dextrin cement hydration regulating material, the mass content of CaO and the mass content of MgO, and the activity value of magnesium oxide; the preparation method of the hydration heat and the particle size of the calcium-magnesium expansion material are not clearly defined. Alternatively, the disclosed material preparation method is to pyrolyze the starch under high temperature conditions and then cool it. On the one hand, this process destroys the three-dimensional structure at high temperature, and on the other hand, the low molecular weight sugars produced by hydrolysis are not removed, and there is a risk of long slow setting at a higher dosage. Summary of the invention
[0009] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a concrete anti-cracking agent suitable for high temperature environments, a preparation method and an application thereof.
[0010] To achieve the above object, the present invention is implemented by adopting the following technical solutions:
[0011] In a first aspect, the present invention provides a concrete anti-cracking agent suitable for high temperature environments, comprising the following components in percentage by weight:
[0012] Calcium oxide expansion material: 45%-65%;
[0013] Magnesium oxide expansion material: 30%-45%;
[0014] Hydration heat regulating materials: 1.5%-5%;
[0015] The balance is gypsum and fly ash in any proportion;
[0016] Among them, the calcium oxide expansion material adopts clinker powder with calcium oxide as the main expansion source, and the oxide composition is as follows: calcium oxide ≥65%, aluminum oxide ≥5%, sulfur trioxide ≥10%, and meets the requirements of 45um square hole sieve residue ≥65%, 80um square hole sieve residue ≥25%, and 10% mortar is added to limit the expansion rate to ≥0.15%; the calcium oxide clinker powder of Jiangsu Subote New Materials Co., Ltd. is preferred.
[0017] The magnesium oxide expansion material adopts light-burned magnesium oxide, and is calcined through a vertical kiln, a rotary kiln or a suspension kiln, according to the oxide composition: magnesium oxide ≥85%, calcium oxide ≤4%, and the 45um square hole sieve residue is ≥45%, the 80um square hole sieve residue is ≤10%, and the active reaction time is 100s-250s; the light-burned magnesium oxide calcined in a suspension kiln of Jiangsu Subote New Materials Co., Ltd. is preferred.
[0018] The reaction of calcium oxide expansion material and magnesium oxide expansion material in cement concrete is not only affected by their own chemical composition, crystal structure, etc., but also as powder materials, the particle size is also a key parameter for the performance. In order to adapt to high-temperature concrete working conditions, in addition to the conventional content and other compositions, the particle size is limited by 45um and 80um sieve residues, further increasing the proportion range of particles with larger particle sizes, wherein particles below 45um are used to exert early expansion effects, and particles above 45um have a delayed expansion effect. In particular, large-particle calcium oxide expansion materials can complement magnesium oxide, which naturally has delayed expansion, to achieve compensatory shrinkage of the concrete throughout the entire process, reduce the risk of cracking, and inhibit concrete cracking.
[0019] The preparation process of the above concrete anti-cracking agent suitable for high temperature environment is simple, and only the components accurately weighed are mixed according to the proportion.
[0020] Furthermore, the preparation method of the hydration heat regulating material is:
[0021] Select one or two or more starch mixtures, place them at a temperature below the gelatinization temperature and use a catalyst to hydrolyze them, and control the concentration of the starch hydrolyzed at a temperature below the gelatinization temperature to be no more than 40%;
[0022] The hydrolysis endpoint is determined based on the type of starch, type and amount of catalytic acid, and reaction temperature history: the reaction can be stopped when the proportion of soluble matter in the starch hydrolysis slurry to the solid used is 45%;
[0023] The hydrolyzed slurry is oxidized by periodic acid compounds to destroy low molecular weight monosaccharides and polysaccharide compounds dissolved in water, and the amount of periodic acid oxide added is 1%-15% of the mass of corn starch;
[0024] The reaction system after periodic acid oxidation can be directly dried into powder by spray drying, air flow drying or oven drying to obtain the hydration heat regulating material.
[0025] The concentration of the starch hydrolyzed below the gelatinization temperature is no more than 40%, and the hydrolysis temperature can be lower than the gelatinization temperature. The gelatinization temperature varies slightly depending on the type of starch, origin, and growing climate conditions. Generally, the initial gelatinization temperature of starch is 55-60°C. Therefore, the preferred hydrolysis reaction temperature is 2°C lower than the gelatinization temperature, and the fluctuation does not exceed 2°C.
[0026] The starch used includes but is not limited to corn starch, wheat starch, rice starch, potato starch, lotus root starch, sorghum starch, etc., preferably one starch; it can also be a mixture of two or more starches; if it is a mixture of two or more starches, the hydrolysis temperature is based on the starch with the lowest initial gelatinization temperature.
[0027] The catalyst used for hydrolysis is one or a mixture of two or more of nitric acid, sulfuric acid and hydrochloric acid of any concentration, and the dosage is 2%-10% of the mass of starch, preferably 4%-6%, calculated based on the effective content.
[0028] The speed of hydrolysis varies according to the type of starch, the type and amount of catalytic acid and the reaction temperature history, so it is difficult to determine the end point by the specific reaction time. The judgment of the hydrolysis end point of this patented technology is: the proportion of soluble matter in the starch hydrolysis slurry to the solid used is 45%, that is, as the reaction proceeds, the molecular weight of starch gradually decreases, and small molecular weight oligosaccharides are gradually produced and dissolved in water, and the proportion of the substance dissolved in the water to the total solid content gradually increases until it reaches 45% and the reaction is stopped.
[0029] Stopping the reaction involves two steps: cooling and neutralization. Neutralization can be performed slowly while cooling, or cooling first and then neutralizing. The neutralization end point pH value is 6.0-8.0. Neutralization can be performed with one or a mixture of two or more of sodium hydroxide or potassium hydroxide aqueous solution, solid sodium carbonate, solid potassium carbonate, and solid calcium carbonate of different concentrations. Temperature reduction can be achieved by adding low-temperature water to the hydrolyzate, or by reducing the temperature of the medium surrounding the hydrolyzate, such as reducing the water temperature in a water bath or replacing the insulation medium in the surrounding jacket with a low-temperature medium.
[0030] The process of periodic acid oxidation treatment of the system after cooling and neutralization is to add one or a mixture of two or more of periodic acid, sodium periodate, and potassium periodate thereto, and react for 0.5h without exceeding the starch gelatinization temperature. The amount of periodic acid oxide added is 1%-15% of the mass of corn starch, preferably 8%-10%.
[0031] The reaction system after periodic acid oxidation can be directly dried into powder to obtain the hydration heat regulating material described in the patent. Drying can be carried out by conventional methods such as spray drying, airflow drying, oven drying, etc. Among them, spray drying and airflow drying belong to instantaneous drying, which has no effect on the material properties, and the obtained product is powdery and does not need any further treatment; if the oven drying method is used, the drying temperature must be controlled not to exceed the temperature during hydrolysis, and further crushing into powder is required afterwards; therefore, instantaneous drying spray drying and airflow drying methods are preferred.
[0032] The preparation process of the above-mentioned hydration heat regulating material uses ordinary natural starch as raw material, and is formed by hydrolysis, periodic acid oxidation and drying. The periodic acid oxidation process is carried out in the solution, and a large amount of soluble low molecular weight sugar compounds with the effect of delaying the setting time of cement are dissolved in the water. This is a component that needs to be minimized and avoided as a hydration heat regulating material. Therefore, most of the known hydration heat regulating material patents use dextrin or its modified products in a certain molecular weight range to inhibit the hydration heat of cement. In actual production, it is necessary to reduce the production of this part of soluble matter as much as possible, or control it by physical separation. Periodic acid compounds are highly soluble in water and have the effect of efficiently oxidizing vicinal diols. This patented technology utilizes this feature, combined with the actual working conditions of starch hydrolysis, and uses extremely water-soluble periodic acid compounds to eliminate low molecular weight sugars with slow setting side effects produced in water by hydrolysis, thereby replacing the physical separation process and avoiding the energy consumption and wastewater generation of separation; and the entire reaction is completed in a reaction vessel, which is efficient, environmentally friendly and has lower energy consumption.
[0033] In a second aspect, the present invention provides a method for preparing a concrete anti-cracking agent as described in any one of the first aspects, comprising the following method steps: preparing a hydration heat regulating material, compounding the hydration heat regulating material with any proportion of calcium oxide-type expansion material and magnesium oxide-type expansion material, and adding any proportion of gypsum and fly ash, and stirring to form a concrete anti-cracking agent suitable for high temperature environment.
[0034] In a third aspect, the present invention provides the use of the concrete anti-cracking agent as described in any one of the first aspects in silicate cement, medium-heat cement, low-heat cement, sulphoaluminate cement and oil well cement.
[0035] The concrete anti-cracking agent suitable for high temperature environment of the present invention can be added together with concrete raw materials such as glue, sand, stone and water and stirred, and the addition amount accounts for 6%-12% of the total mass of the glue; the prepared concrete is suitable for various working conditions, especially for high temperature environment with stirring temperature and ambient temperature exceeding 30°C.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The concrete anti-cracking agent and hydration heat regulating material provided by the patent of the present invention do not contain retarding low molecular weight sugars, which can effectively inhibit the hydration heat release rate of cement concrete at various temperatures, and are particularly suitable for cement hydration in high temperature environments, avoiding the long retarding phenomenon caused by oligosaccharides in normal temperature hydration heat regulating materials at high temperatures, and effectively reducing the temperature rise value of concrete in various working conditions including high temperature environments, as well as the risk of temperature shrinkage and cracking caused by temperature rise.
[0038] In addition, the hydration heat regulating material of the present invention is compounded with any proportion of calcium oxide expansion material and magnesium oxide expansion material to form a concrete anti-cracking agent suitable for high temperature environment. It not only has the performance of reducing temperature shrinkage, self-shrinkage and drying shrinkage, but also can effectively improve the expansion efficiency of calcium magnesium expansion material, producing a positive synergistic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The molecular weight distribution (GPC) of the three samples of the same concentration: comparative sample 1 and example samples 1 and 2;
[0040] Figure 2 The hydration temperature rise curves of mortar with three hydration heat control material samples with the same dosage at 30℃. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0042] Preparation of comparative sample and sample of embodiment of the present invention (hydration heat regulating material): Under stirring condition, 60g corn starch with ordinary moisture content of 10%, 37g water and 3g nitric acid are mixed to form slurry, placed in a 56°C water bath for heating, and sampled and tested the solid content of the slurry and the solid content of the centrifuged supernatant at regular intervals until the proportion of the substance dissolved in the water to all solid content reaches 45%. The hydrolyzed solution is cooled and neutralized with solid sodium carbonate to pH=7.4. The neutralized solution is divided into 3 parts, one part is directly dried and ground to form sample 1, marked as comparative sample 1; one part is added with 5% sodium periodate of the corresponding mass of corn starch, stirred for 0.5h and then dried and ground to form sample 2, marked as embodiment sample 1; one part is added with 10% sodium periodate of the corresponding mass of corn starch, stirred for 0.5h and then dried and ground to form sample 3, marked as embodiment sample 2.
[0043] Among the above three samples of hydration heat regulating materials, No. 1 is a comparative sample 1 containing more soluble low molecular weight sugar compounds, and samples 2 and 3 are respectively example samples after being oxidized with periodic acid of different masses based on the comparative sample 1 according to the technology of the present invention. The molecular weight distribution of the three samples at the same concentration is as follows Figure 1 As shown, in the GPC curve, the shorter the elution time, the larger the molecular weight, the longer the elution time, the smaller the molecular weight, the main peak with an elution time of 15-20min is basically similar, but the low molecular weight region with a longer elution time is significantly different, as shown in the figure in the middle, the glucose peak decreases significantly with the increase in the amount of periodic acid, which means that the corresponding glucose concentration is lower; the peak height (concentration) of the remaining low molecular weight substances with an elution time of 20-25min also decreases significantly. This result shows that the technical solution is in accordance with expectations, and the use of periodic acid compounds significantly reduces the soluble low molecular weight sugar compounds, providing a material basis for reducing the long slow coagulation problem caused by them.
[0044] According to the method in the JC / T 2608-2021 "Concrete Hydration Temperature Rise Inhibitor" standard, the effects of the above three hydration heat control material samples on the hydration temperature rise of mortar at 30°C were tested. The results are as follows: Figure 2 As shown. The temperature setting of 30°C is intended to simulate the actual working conditions of cement-based materials under high temperature environments. The peak temperature of the baseline mortar without samples is close to 47°C. After adding the three samples, the temperature rise values of the mortar are significantly reduced, all of which can be reduced to about 40°C. In addition to the reduction in the peak temperature, the time when the temperature rise starts is also significantly extended, which means that the setting time is longer. The temperature rise time of the sample of comparative example 1 that is not treated with periodic acid is about 36h, and the temperature rise time of the mortar of example samples 1 and 2 modified with different periodic acids is 30h and 15h. In comparison, the temperature rise time (i.e., the setting time) is significantly shortened; the negative consequences brought about by the soluble low-molecular-weight sugar compounds therein are greatly alleviated.
[0045] The above three samples were mixed with calcium oxide clinker and light-burned magnesium oxide of Jiangsu Subote New Materials Co., Ltd. according to the same formula (calcium oxide: magnesium oxide: hydration heat control material: gypsum = 50:35:2:13) to prepare three concrete anti-cracking agent products. The relevant performance indicators were tested in accordance with T / CECS10082-2020 "Calcium-magnesium composite expansion agent for concrete". The results are shown in Table 1 below.
[0046] It can be seen from the table that the performance of the anti-cracking agents prepared with the three samples of hydration heat regulation materials is significantly different. In terms of setting time, the retarding effect of the hydration heat regulation material results in a longer setting time for the three anti-cracking agents. In comparison, the setting time of the anti-cracking agent prepared with the example sample modified with periodic acid is relatively shorter. Due to the long setting time and the slow development of early strength caused by hydration heat regulation, the restricted expansion rate in 20°C water is relatively low, but the shorter the setting time, the higher the restricted expansion rate; the difference (△ε) between the restricted expansion rate of curing for 21d in 20°C air and curing for 28d in 60°C water is basically consistent with the restricted expansion rate of curing for 3d. For the strength at a longer age, although the regularity remains the same, the magnitude of the difference is significantly narrowed.
[0047] Table 1 Performance results of anti-cracking agents added to samples of three hydration heat regulating materials
[0048]
[0049] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A concrete anti-cracking agent suitable for high temperature environments, characterized in that: Includes the following mass percentage components: Calcium oxide expansion material: 45%-65%; Magnesium oxide expansion material: 30%-45%; Hydration heat regulating materials: 1.5%-5%; The balance is gypsum and fly ash in any proportion; The calcium oxide expansion material adopts clinker powder with calcium oxide as the main expansion source, and the oxide composition is as follows: calcium oxide ≥ 65%, aluminum oxide ≥ 5%, sulfur trioxide ≥ 10%, and the residue on the 45um square hole sieve is ≥ 65%, the residue on the 80um square hole sieve is ≥ 25%, and the expansion rate of 10% mortar added is limited to ≥ 0.15%; The magnesium oxide expansion material adopts light-burned magnesium oxide, and is calcined in a vertical kiln, a rotary kiln or a suspension kiln, according to the oxide composition: magnesium oxide ≥85%, calcium oxide ≤4%, and meets the requirements of 45um square hole sieve residue ≥45%, 80um square hole sieve residue ≤10%, and the active reaction time is 100s-250s.
2. The concrete anti-cracking agent suitable for high temperature environment according to claim 1, characterized in that: The preparation method of the hydration heat regulating material is: Select one or two or more starch mixtures, place them at a temperature below the gelatinization temperature and use a catalyst to hydrolyze them, and control the concentration of the starch hydrolyzed at a temperature below the gelatinization temperature to be no more than 40%; The hydrolysis endpoint is determined based on the type of starch, type and amount of catalytic acid, and reaction temperature history: the reaction can be stopped when the proportion of soluble matter in the starch hydrolysis slurry to the solid used is 45%; The hydrolyzed slurry is oxidized by periodic acid compounds to destroy low molecular weight monosaccharides and polysaccharide compounds dissolved in water, and the amount of periodic acid oxide added is 1%-15% of the mass of corn starch; The reaction system after periodic acid oxidation can be directly dried into powder by spray drying, air flow drying or oven drying to obtain the hydration heat regulating material.
3. The concrete anti-cracking agent suitable for high temperature environment according to claim 2, characterized in that: Determining the hydrolysis stop reaction includes two steps: cooling and neutralization. Neutralization is performed slowly while cooling, or cooling first and then neutralizing. The neutralization endpoint pH value is 6.0-8.
0. Neutralization uses one or a mixture of two or more of sodium hydroxide or potassium hydroxide aqueous solution, sodium carbonate solid, potassium carbonate solid, and calcium carbonate solid of different concentrations; The cooling method is to add low-temperature water to the hydrolyzate or to lower the temperature of the medium around the hydrolyzate.
4. The concrete anti-cracking agent suitable for high temperature environment according to claim 2, characterized in that: The starch includes corn starch, wheat starch, rice starch, potato starch, lotus root starch or sorghum starch.
5. The concrete anti-cracking agent suitable for high temperature environment according to claim 2, characterized in that: The catalyst is one or a mixture of two or more of nitric acid, sulfuric acid and hydrochloric acid of any concentration, and the dosage thereof is 2%-10% of the mass of starch based on the effective content thereof.
6. The method for preparing the concrete anti-cracking agent according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: preparing a hydration heat regulating material, compounding the hydration heat regulating material with any proportion of calcium oxide expansion material and magnesium oxide expansion material, adding any proportion of gypsum and fly ash, and stirring to form a concrete anti-cracking agent suitable for high temperature environment.
7. The concrete anti-cracking agent according to any one of claims 1 to 5 is used in silicate cement, medium-heat cement, low-heat cement, sulphoaluminate cement and oil well cement.
Citation Information
Patent Citations
and application of concrete expansion agent for compensating concrete dry shrinkage
CN101643333B
Preparation method of calcium oxide expansion agents
CN101774777B
Compound expanding agent and application thereof in blocking concrete for diversion tunnel
CN101786819A
Plastic concrete water evaporation inhibitor and preparation method thereof
CN101805145B
Comb copolymer shrinkage reducing agent and preparation method thereof
CN102030872A
Cited By
Magnesium oxide-based low-temperature expanding agent as well as preparation method and application thereof
CN121202479A
Anti-erosion expansion anti-cracking agent for concrete and preparation method of anti-erosion expansion anti-cracking agent
CN122102558A